Adult attachment orientations and well-being during the transition to parenthood. (February 2019) - Simpson, Jeffry A; Rholes, W Steven
Highlights: Reviews how adult attachment orientations predict outcomes across the transition to parenthood. Discusses why chronic stress evokes different concerns in anxious and avoidant people. Frames current findings within the Attachment Diathesis-Stress Process Model. Proposes promising directions for future research. Abstract : In this article, we discuss theory and research on how people who have different adult romantic attachment orientations fare across one of life's often happiest, but also most chronically stressful, events — the transition to parenthood. We first discuss central principles of attachment theory and then review empirical research revealing how two types of attachment insecurity — anxiety and avoidance — tend to prospectively predict unique patterns of relational and personal outcomes across this often challenging life event. We also suggest how many of these findings can be understood within a diathesis-stress process model that has guided our own research on the transition to parenthood.